Silver colloids as plasmonic substrates for direct label-free surface-enhanced Raman scattering analysis of DNA. Issue 17 (23rd May 2016) - Torres-Nuñez, A.; Faulds, K.; Graham, D.; Alvarez-Puebla, R. A.; Guerrini, L.
Abstract : Unraveling the role played by the surface chemistry of silver colloids in the direct SERS analysis of DNA. Abstract : Ultrasensitive direct SERS analysis offers a powerful analytical tool for the structural characterization and classification of nucleic acids. However, acquisition of reliable spectral fingerprints of such complex biomolecules poses important challenges. In recent years, many efforts have been devoted to overcome these limitations, mainly implementing silver colloids as plasmonic substrates. However, a reliable cross-comparison of results reported in the recent literature is extremely hard to achieve, mostly due to the broad set of different surface properties of the plasmonic nanoparticles. Herein, we perform a thorough investigation of the role played by the metal/liquid interface composition of silver colloids in the direct label-free SERS analysis of DNA. Target molecules of increasing complexity, from short homopolymeric strands to long genomic duplexes, were used as probes. We demonstrate how apparently subtle changes in the colloidal surface chemistry can dramatically modify the affinity and the final SERS spectral profile of DNA. This has significant implications for the future design of new analytical strategies for the detection of DNA using SERS without labels.